In Vitro and In Vivo Performance of Novel Spray Dried Andrographolide Loaded Scleroglucan Based Formulation for Dry Powder Inhaler - Mali, Ashwin J.; Bothiraja, Chellampillai; Purohit, Ravindra Nandlal; Pawar, Atmaram Pandurang (Current Drug Delivery, 2017)
Background: Current therapy for pulmonary arterial hypertension (PAH) is unable to prevent progression of disease due to continuous infusions and multiple oral administrations. This resulted in the need of novel treatment which would target directly structural vascular changes that weaken blood flow through pulmonary circulation. Objective: The objective of present study was to develop spray dried (SD) formulation for dry powder inhaler (DPI) with enhanced aerosol performance and lung deposition by using novel bioactive, andrographolide (AGP) and carrier, scleroglucan (SCLG) with improved antihypertensive activity. The SDAGP formulation was evaluated for physicochemical properties and in vitro/in vivo lung deposition. Further, antihypertensive activity was studied by monocrotaline (MCT) induced rat model. Results: The SDAGP exhibited mean median aerodynamic diameter (MMAD) and fine particle fraction (FPF) of 3.37 ± 0.47 μm and 60.24 ± 0.98%. The in vivo absorption profile of final formulation reflected increased lung deposition of AGP at the end of 24 h with no signs of inflammation and toxicity. Moreover, SDAGP formulation confirmed enhanced antihypertensive activity. Conclusion: The results proved use of AGP and SCLG as a novel bioactive and carrier with enhanced lung deposition and pulmonary antihypertensive activity.
Keywords: pulmonary arterial hypertension (PAH)